2016
DOI: 10.1016/j.ydbio.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Postotic and preotic cranial neural crest cells differently contribute to thyroid development

Abstract: Thyroid development and formation vary among species, but in most species the thyroid morphogenesis consists of five stages: specification, budding, descent, bilobation and folliculogenesis. The detailed mechanisms of these stages have not been fully clarified. During early development, the cranial neural crest (CNC) contributes to the thyroid gland. The removal of the postotic CNC (corresponding to rhombomeres 6, 7 and 8, also known as the cardiac neural crest) results in abnormalities of the cardiovascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“… Teshima et al (2016) also found that conditional inactivation of Fgf10 in neural crest ( Wnt1Cre;Fgf10 fl/fl mutants) reduced thyroid size although to a lesser degree than after global inactivation, suggesting that mesodermal Fgf10 also likely contributes to thyroid development. Nonetheless, this study and ours localized Fgf10 to crest-derived mesenchyme that invests the thyroid primordium, which provides mechanistic insight to thyroid developmental defects reported to occur after neural crest ablation ( Bockman and Kirby, 1984 ; Kameda et al, 2013 ; Maeda et al, 2016 ). It is important to note that the phenotype of Fgf10 null mutant mice does not comprise thyroid agenesis, which was originally reported ( Ohuchi et al, 2000 ) and thus erroneously stated in a recent review paper on the multifunctional role of Fgf10 in development ( Itoh, 2016 ).…”
Section: Discussionmentioning
confidence: 56%
“… Teshima et al (2016) also found that conditional inactivation of Fgf10 in neural crest ( Wnt1Cre;Fgf10 fl/fl mutants) reduced thyroid size although to a lesser degree than after global inactivation, suggesting that mesodermal Fgf10 also likely contributes to thyroid development. Nonetheless, this study and ours localized Fgf10 to crest-derived mesenchyme that invests the thyroid primordium, which provides mechanistic insight to thyroid developmental defects reported to occur after neural crest ablation ( Bockman and Kirby, 1984 ; Kameda et al, 2013 ; Maeda et al, 2016 ). It is important to note that the phenotype of Fgf10 null mutant mice does not comprise thyroid agenesis, which was originally reported ( Ohuchi et al, 2000 ) and thus erroneously stated in a recent review paper on the multifunctional role of Fgf10 in development ( Itoh, 2016 ).…”
Section: Discussionmentioning
confidence: 56%
“…It should be noted that, although important for morphogenesis, embryonic vessels do not have an inductive role for the thyroid, as shown in the zebrafish cloche mutant which is devoid of any vascularization . Classical ablation studies in chick embryos have also revealed a role for cranial neural crest in thyroid development (Bockman and Kirby, 1984), and more recent findings indicate that subpopulations of neural crest cells differentially influence the distinct stages of chick thyroid morphogenesis (Maeda et al, 2016). This again highlights that the embryonic thyroid shifts microenvironments more than once before reaching its final position in the neck, and thus is likely -as we indeed highlight below and as summarized in Fig.…”
Section: Extrinsic Factors That Regulate Thyroid Morphogenesismentioning
confidence: 59%
“…Finally, it should be noted that ablation studies in chick embryos have shown that neural crest-derived mesenchyme regulates thyroid lobe formation independently of embryonic vessels (Maeda et al, 2016). A thyroid lobe defect may thus appear even though the pharyngeal arch arteries seemingly develop normally.…”
Section: Blood Vessel-mediated Control Of Thyroid Morphogenesismentioning
confidence: 99%
“…Disruption of this signaling results in abnormally small mandibular and hyoid arches, absence of the NC‐derived Meckel's cartilage, small tongue, and malformed or missing middle ear elements (Clouthier et al, ; Pla & Larue, ; Yanagisawa et al, ). It was also found that Edn1/EdnrA ‐knockout mouse and bosentan‐treated chick embryos showed an alteration in the bilobation process during thyroid development, with some embryos displaying only single‐lobe formation (Kempf et al, ; Maeda et al, ). Additionally, defects in NC migration to pharyngeal arches 3, 4 and 6 caused by Edn1/Ednra inhibitors give rise to cardiac outflow tract malformations (Kurihara et al, ; Pla & Larue, ).…”
Section: Chemical Agentsmentioning
confidence: 99%